Effect of row spacing and planting date on the yield and agronomic characteristics of soybean at Dourados, MS - Melhorança, André Luiz; Mesquita, Airton Nonemacher de (Pesquisa Agropecuaria Brasileira, 2014)
Having in mind that a row spacing may affect grain yield and result in agronomic characteristics more adequate for the mechanical harvesting of soybean (Glycine max (L.) Merrill) during different planting time and for different cultivars, an experiment was conducted during the agricultural years of 1976/77, 1977/78 an 1978/79, at Dourados, MS, Brazil. The results indicated that the height of the plants and the height of the attachment of the first legume were not affected by the various spacings used. There were no row spacing effect on grain yield. There were differences among planting dates and a decrease in yield was observed between planting made on 15 of October and that made on 15 of December. The length of the periods of development (emergence to flowering and emergence to maturity) were not influenced by the different row spacing. The agronomic characteristics were compatible for the mechanical harvesting in all the planting dates and row spacing studied.